Islamic Banks and Financial Stability : An Empirical Analysis - Cihak, Martin (IMF Working Papers; Working Paper ;, 2008)
The relative financial strength of Islamic banks is assessed empirically based on evidence covering individual Islamic and commercial banks in 18 banking systems with a substantial presence of Islamic banking. We find that (i) small Islamic banks tend to be financially stronger than small commercial banks; (ii) large commercial banks tend to be financially stronger than large Islamic banks; and (iii) small Islamic banks tend to be financially stronger than large Islamic banks, which may reflect challenges of credit risk management in large Islamic banks. We also find that the market share of Islamic banks does not have a significant impact on the financial strength of other banks.